Efficiency and exergy analysis of a new solar air heater - Kurtbas, I; Durmus, A (Pergamon-Elsevier Science Ltd, 2004)
It would be misleading to consider only the cost aspect of the design of a solar collector. High service costs increase total costs during the service life of solar collector. The most effective way to save energy is by increasing the efficiency in a solar collector by the heat transfer coefficient. In our study, five solar collectors with dimensions of 0.9 x 0.4 in were used and the flow line increased where it had narrowed and expanded geometrically in shape. These collectors were set to four different cases with dimensions of I x 2 in. Therefore, heating fluids exit the solar collector after at least 4.5 m displacement. According to the collector geometry, turbulence occurs in fluid flow and in this way heat transfer is increased. The results of the experiments were evaluated on the days with the same radiation. The efficiencies of these four collectors were compared to conventional flat-plate collectors. It was seen that heat transfer and pressure loss increased depending on shape and numbers of the absorbers. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: air collector; collector efficiency; exergy loss